Optimasi Pencarian Rute Terpendek pada Provinsi Bali Menggunakan Algoritma Genetika - Muhammad Caesar Gilang Indrawan; I Made Widiartha (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Bali is one of the most popular tourist destinations in Indonesia. Therefore, many local and international tourists visit Bali for holidays. Searching for the shortest route is needed for tourists who want to take a walk around the island of Bali. By getting the shortest route between the initial location and the destination location, the efficiency level of time needed to travel between the two locations will be better. Searching for the shortest route can be done by applying a genetic algorithm. Genetic algorithm is a method or technique of optimization and search based on the mechanism of natural genetic principles and natural selection.